2022
DOI: 10.1002/anie.202204046
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption in Reversed Order of C2 Hydrocarbons on an Ultramicroporous Fluorinated Metal‐Organic Framework

Abstract: Metal-organic frameworks have been widely studied in the separation of C 2 hydrocarbons, which usually preferentially bind unsaturated hydrocarbons with the order of acetylene (C 2 H 2 ) > ethylene (C 2 H 4 ) > ethane (C 2 H 6 ). Herein, we report an ultramicroporous fluorinated metal-organic framework Zn-FBA (H 2 FBA = 4,4'-(hexafluoroisopropylidene)bis(benzoic acid)), shows a reversed adsorption order characteristic for C 2 hydrocarbons, that the uptake for C 2 hydrocarbons of the framework and the binding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 57 publications
0
30
0
Order By: Relevance
“…The selectivity for equimolar C 2 H 6 /C 2 H 4 mixtures is 1.30 at 298 K and 100 kPa (Figure a). Although this C 2 H 6 /C 2 H 4 selectivity at 298 K is lower than some famous MOFs, such as BUT-315-a (2.35), MIL-142A (1.5), and Zn-FBA (2.9), it is comparable to Zn-atz-oba (1.27) and LIFM-28 (1.24) . In addition, the separation potential (Δ q = q 1 y 2 / y 1 – q 2 ) is utilized to further assess C 2 H 6 /C 2 H 4 separation performance, which as a comprehensive index integrating adsorption capacity and selectivity is proposed by Krishna first and provides a convenient and simple indicator for the separation ability of MOFs based on IAST.…”
Section: Resultsmentioning
confidence: 92%
“…The selectivity for equimolar C 2 H 6 /C 2 H 4 mixtures is 1.30 at 298 K and 100 kPa (Figure a). Although this C 2 H 6 /C 2 H 4 selectivity at 298 K is lower than some famous MOFs, such as BUT-315-a (2.35), MIL-142A (1.5), and Zn-FBA (2.9), it is comparable to Zn-atz-oba (1.27) and LIFM-28 (1.24) . In addition, the separation potential (Δ q = q 1 y 2 / y 1 – q 2 ) is utilized to further assess C 2 H 6 /C 2 H 4 separation performance, which as a comprehensive index integrating adsorption capacity and selectivity is proposed by Krishna first and provides a convenient and simple indicator for the separation ability of MOFs based on IAST.…”
Section: Resultsmentioning
confidence: 92%
“…The adsorption capacities of C 2 H 6 in ZUL-C3 and ZUL-C4 were 2.30 mmol/g (1.26 molecule per cell) and 2.93 mmol/g (1.58 molecule per cell) at 298 K, 100 kPa, while those of C 2 H 4 were 1.53 mmol/g (0.88 molecule per cell) and 1.70 mmol/g (0.91 molecule per cell), respectively. The C 2 H 6 / C 2 H 4 uptake ratio for ZUL-C3 reached 1.50 and for ZUL-C4 reached 1.72, which surpassed many top-performing C 2 H 6preferring adsorbents, like FJI-H11-Me(des) (1.24), 4 Fe 2 (O 2 )-(dobdc) (1.26),9 and Zn-FBA (1.10) 46. Besides, it is worth noting that a slight "adsorption step" was observed in the C 2 H 6 isotherm of ZUL-C4 at about 95 kPa, 298 K. With the temperature decreasing to 273 K, "adsorption steps" appeared in both MOFs because the higher adsorption amount at lower temperature induced a framework lattice transformation at relatively low pressures.…”
mentioning
confidence: 92%
“…10−16 A recent analysis of interactions involving C−F in terms of their frequency of occurrence in molecular crystal structures by Cole and Taylor indicated that the intramolecular bonding environment strongly influenced the fluorine interactions and their contributions to crystal packing. 17 molecules forming pentamer, hexamers, and heptamers in the gas phase (detected using microwave spectroscopy) 18 and hydrocarbon adsorption in fluorinated metal−organic frameworks 19 underscore the role of C−H•••F interactions in contexts beyond crystal packing. It has been reported that 18% of the protein−ligand complexes have fluorine-containing hydrogen bonding interactions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The notion that organic fluorine does not participate in intermolecular hydrogen bonding (with no apparent effects on the stability of crystal packing) has been critically investigated by several researchers. For example, Desiraju et al have shown the definite role of C–H···F–C hydrogen bonds in crystal packing, thus challenging this notion. Further, the contributions from Row, Choudhury, Chopra, and co-workers have by now established the ubiquity of a variety of supramolecular interaction motifs involving organic fluorine. A recent analysis of interactions involving C–F in terms of their frequency of occurrence in molecular crystal structures by Cole and Taylor indicated that the intramolecular bonding environment strongly influenced the fluorine interactions and their contributions to crystal packing . The results on the molecular self-aggregation of difluoromethane molecules forming pentamer, hexamers, and heptamers in the gas phase (detected using microwave spectroscopy) and hydrocarbon adsorption in fluorinated metal–organic frameworks underscore the role of C–H···F interactions in contexts beyond crystal packing. It has been reported that 18% of the protein–ligand complexes have fluorine-containing hydrogen bonding interactions .…”
Section: Introductionmentioning
confidence: 99%